Pengaruh Konsentrasi Oksidator pada Proses Hidroksilasi Minyak Jarak (Castor Oil) Dengan atau Tanpa Proteksi Gugus Hidroksi - Marlina Marlina; N. M. Surdia; C. L. Radiman; S. Achmad (Journal of Mathematical and Fundamental Sciences, 2004)
Oil is derived from the bean of castor plant ricinus communis l., belonging to euphorbiaceae family. Oil rendement per gram of castor bean is 45 "“ 48 % with hight pure product and better than standard resulted by The Association of Official Analytical Chemistry (AOAC). The main components in castor oil are oleic, palmitic and resinoleic acid. Protection process by acetylation occurs well on hydroxyl group of castor oil, indicated by increasing of iodine number and decreasing of hydroxyl number. Oxidation process is more efective on protected oil than non protected oil. The excess of oxidator concentration changed the product to be aldehide and carboxylic acid. Optimum condition was reached when oxidator concentration was 15 %, with hydroxyl value of 1280.438 mg/g and iodine number of 33.093 mg/g.